Applying Importance Performance Analysis to Assess Customer Satisfaction: Mass Rapid Transportation in Indonesia - Oktaveana Sugiarti Tjitrohartoko; Trisha Gilang Saraswati (Research Synergy Foundation, 2020)
Jakarta, which is the capital city of Indonesia is a city with traffic jam number 7 in the world. Therefore, the government provides mass transportation solutions in the form of Mass Rapid Transportation with the hope that it can unravel congestion and become safe and comfortable transportation for society. However, there are still many complaints about the services provided by Mass Rapid Transportation and affect customer satisfaction. (2) The purpose of this study is to demonstrate important performance analysis as a decision-making tool for the transportation industry in terms of customer satisfaction and to assess the performance of mass rapid transportation in performing their services to satisfy their customers. (3 Importance Performance Analysis was used to measure the level of customer satisfaction through measurements of customer expectation and reality. The sample of 100 respondents was obtained based on the sampling criteria which are only people who have used Mass Rapid Transportation in Indonesia at least one time that can fill the questionnaire. (4) Importance Performance Analysis (IPA) in this study successfully identified each attribute on customer satisfaction. The researcher is aware that the impact of an attribute is significantly varied with the different levels of performance on each attribute. By using IPA, the company of Mass Rapid Transportation in Indonesia can map what needs to be improved, maintained, to be kept, and to be reduced as an effort to increase customer satisfaction.